Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires